Notes on the genus Diarsia with description of a new species from China (Lepidoptera: Noctuidae) - Gyulai, Peter; Saldaitis, Aidas (Zootaxa, 2020)
In 2019, the authors of the present paper presented a detailed study on the genus Diarsia Hübner, 1816, giving an overview on the distribution, research history and the comprehensive studies and generic classification of the genus, including the description of seven new species (Gyulai & Saldaitis, 2019). In that paper, one of the newly described species was Diarsia zillii Gyulai & Saldaitis, 2019, based on a single male specimen. Since, a further male and a female were found in the collected stored material, almost from the same locality and date. The genitalia dissection confirmed that the description was necessary and correct. Thus, the colour image of the female and the short characterisation of the female genitalia are given in the present paper.